Bismuth sulfide (Bi2S3) nanotubes decorated TiO2 nanoparticles heterojunction assembly for enhanced solar light driven photocatalytic activity. Issue 15 (15th November 2016) - Kumar, Sandeep; Sharma, Shelja; Sood, Swati; Umar, Ahmad; Kansal, Sushil Kumar
Abstract: In this work, we report the synthesis of TiO2 nanoparticles coupled with a metal sulfide semiconductor having narrower band gap i.e. Bi2 S3, so as to utilize the maximum fraction of sunlight and to improve the photocatalytic performance of TiO2 . Bi2 S3 nanotubes-TiO2 nanoparticle heterostructures were successfully synthesized using a facile solvothermal process. The composition, morphology, optical and pore structural properties of the as prepared photocatalyst were studied by various techniques such as powder X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), fourier transformation infra-red spectroscopy (FTIR), photoluminescence spectroscopy (PL) and Brunauer-Emmett-Teller (BET) surface area analysis. It was observed that the synthesized heterostructures were composed of high density of TiO2 nanoparticles along with Bi2 S3 nanotubes. The hetero-nanostructures composed of crystalline anatase TiO2 and orthorhombic Bi2 S3 were synthesized, with high visible light response and surface area. The synthesized heterostructured photocatalyst was further explored for the degradation of a toxic azo dye i.e. amaranth dye under solar light and it exhibited superior photocatalytic activity as compared to bare Bi2 S3 and TiO2 . Graphical abstract: Highlights: Facile solvothermal preparation of Bi2 S3 -TiO2 heterostructures. Possess high crystallinity, purity, large surface area and good optical properties. A potential solar light driven photocatalyst.